HUBUNGAN ANTARA KENYAMANAN PELAYANAN DENGAN LOYALITAS PELANGGAN: STUDI PADA MAHASISWA UNIVERSITAS DIPONEGORO PENGGUNA LAYANAN GO-JEK DI SEMARANG - SANJAYA, LUKMAN JEFRI (Faculty of Psychology, Diponegoro University, 2017)
The development of smartphone users in Indonesia has opened the opportunity to grow up manysupport application. This phenomenon was utilized by some business player to increase their service through technology, including Go-Jek.This research goal is finding out relationship between service convenience and customer loyaltyof undergraduate students of Diponegoro University who have usedGo-Jek service in Semarang. One hundredsamples with characteristics undergraduate students of Diponegoro University who have used Go-Jek service in Semarang at least twice was selected by quota sampling. Based on data collection, subjectâ€™s age between 18-24years old(M = 20.79, SD = 1.40) consist of17% maleand 83% female. Data collection used Likert scale consist of Service Convenience Scale(30 items, Î± = .92) andCustomer Loyalty Scale (27 items, Î± = .90). The result of simple linear regression analysis shows that there is positive and significant relationship between service convenience and customer loyalty indicated byr = .50 (p < .001). It means that customer with higher service convenience will have higher customer loyalty too.Service convenience giveseffect contribution of 24.50% toward customer loyalty. This research result is worthwhile as reference to future research about antecedents of customer loyalty. Toward businessman,it is useful as reference to maintain their customers.Â Â